Development of Animated Video Learning Media Based on Sparkol VideoScribe to Increase Elementary School Students' interest in Learning - Anggraeni, Oki; Triyono, Bambang (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, 2023)
Conventional learning activities using only a blackboard, the lecture method are now starting to cause problems in several elementary schools, the learning media used does not increase students' interest in learning, resulting in difficulty understanding the material and easily getting bored in the learning process. The aim this research is to determine the process of developing animated video learning media based on Spakrol Videoscrabe, to determine the feasibility of animated videos learning media based on Spakrol Videoscrabe and to determine the learning interest of elementary school students. Sparkol VideoScribe-based animated videos media is media in the form of Mp4 videos, where the video itself contains material that is interconnected with animated images, charts, and there is sound in the video. This type of research is included in a comparative quantitative research design with a quasi-experimental approach. The data collection method is through the questionnaire/questionnaire method. The effectiveness level analysis technique uses t-test. The research results show that the experimental clas has highers results than the control class with a t-test value for the control clas of 70.00 and the experimental class of 80.22 and for the variable student interest in learning based on a simple regression test the results state that 0.05 < 0.054 so Ho is rejected Ha is accepted, which means there is an influence on the learning outcomes of elementary school students.